From Imagining to Wearing: artistic processes and experiments on the rite of passage – marriage - Almeida, Elaine Karla de; Augusto, Michele Dias (Farol, 2024)
We present a summary of the creative process of the artistic project “Mirar-Imaginar-Vestir”, an interdisciplinary approach from the fields of fashion, performing arts and interactive installation, with the aim of exploring the symbolic, social and affective concepts of the rite of passage of wedding, through the memory of the collections of the National Costume Museum (MNT) and the National Dance Theater Museum (MNTD) - bridal costumes and dances based on the romance of Inês de Castro and Pedro I, from Portugal.